Regulation and Roles of Urocortins in the Vascular System - Kazunori Kageyama; Ken Teui; Naoki Tamasawa; Toshihiro Suda (International Journal of Endocrinology)
Urocortins (Ucns) are members of the corticotropin-releasing factor (CRF) family of peptides. Ucns would have potent effects on the cardiovascular system via the CRF receptor type 2 (CRF2 receptor). Regulation and roles of each Ucn have been determined in the vascular system. Ucns have more potent vasodilatory effects than CRF. Human umbilical vein endothelial cells (HUVECs) express Ucns1-3 mRNAs, and the receptor, CRF2a receptor mRNA. Ucns1-3 mRNA levels are differentially regulated in HUVECs. Differential regulation of Ucns may suggest differential roles of those in HUVECs. Ucn1 and Ucn2 have strong effects on interleukin (IL)-6 gene expression and secretion in rat aortic smooth muscle A7r5 cells. The increase that we observed in IL-6 levels following Ucn treatment of A7r5 cells suggests that smooth muscle cells may be a source of IL-6 secretion under physiological stress conditions. Ucns are important and unique modulators of vascular smooth muscle cells and act directly or indirectly as autocrine and paracrine factors in the vascular system.